MANAGEMENT OF PILONIDAL DISEASE AND COCCYGEAL DERMOID CYSTS - O. Yurkiv; Ie. V. Tsema (Bogomolets National Medical University, 2018)
Summary. An analysis of national and foreign literature about etiology and pathogenesis of pilonidal disease has been performed. Particular attention is paid to the modern concept of acquired origin of pilonidal disease. Modern data about epidemiology, etiopathogenesis and classification of a pilonidal disease have been presented. The results of surgical treatment of pilonidal cysts are shown. Priority of modern etiopathogenetically grounded approaches to surgical treatment of this pathology based on fundamentally new technical techniques such as Gips-technique, Lord-Millar technique, EPSiT, Bascom II operation (cleft-lift) has been presented. The present ideas about coccygeal dermoid (teratomas) and differences in the approaches to surgical treatment compared with the pilonidal cyst are explained.